Voice in the discussion about the original architecture of the Powder Tower and the 16th century third defensive line in the Lviv Middletown - Bevz, Mykola (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The Powder Tower was an integral part of the third defensive line, which was laid around the Lviv City Centre since 1522. The active phase of construction of the third line begins after 1527 (the Great Fire of Lviv) and continues until the end of 1540. Construction took place during twenty years when the city was exempt from paying taxes to the state royal treasury and could spend money on the modernization of fortifications. In the article, we prove that the date of its construction should be considered 1522−1535 based on the analysis of the defensive parameters of the Powder Tower, its architectural and typological characteristics. Although in the literature most often we can find that construction of the tower was conducted in 1554−1556. In my opinion, at this time there could only be some kind of modernization of the building – the construction of an additional last tier, covering galleries or installing a roof over the entire building. A defence facility of such cubic capacity could not be built in 2 or 3 years. Therefore, given the Great Fire in the city in 1527, the following dating scheme looks very logical: the beginning of work – in 1522, completion – in 1535 and modernization – in 1554−1556. The environment around the Powder Tower, in addition to the extraordinary value of architectural space, has preserved archaeological remains of a unique complex of fortifications of the XIV-XVI centuries. Improvement and and architectural and landscape transformations of the territory around the Powder Tower should be considered as a complex regeneration of the eastern side of the fortifications of the Lviv city centre, which consisted of three defensive lines: a High wall (from the port Ruthenica, Mulyarska and Rymarska towers), a Low wall with three small bastei, the Third belt of fortifications. Unlike the Low wall, the third defensive line of artillery bastions surrounds the city centre on all four sides. The third belt of fortifications had constant phases of modernization and reconstruction. After its construction in 1522−1540 and modernization in 1554−1556 and further reconstruction of its individual objects took place. For example, in the eastern part of the third line: the north-eastern rondel eventually became the Royal belleward; the empty Powder Tower at the beginning received the upper tier with machicolations, and later the roof; the Carmelite entrance was gradually transformed due to the standards of the defensive gate; the triangular bastei was rebuilt into a “fifth-form” bastion; the Royal Rondel in the south-eastern corner of the defensive belt received a high upper part.